Estimation of Time Since Death by using Algorithm in Early Postmortem Period - Poposka, Verica; Gutevska, A.; Stankov, Aleksandar; Pavlovski, Goran; Jakjovski, Zlatko; Janeska, B. (Global Journals Inc. (USA), 2013)
Estimation of the time since death in the early post mortem period is performed by analysis of the supravital signs and the early signs of death. Using several methods for determining the time since death increases significantly the preciseness and reliability upon estimation of the time since death. The objective of this paper is to find a way for faster and more simple estimation of the time since death by using several parameters. At the Institute of Forensic Medicine and Criminology an analysis of five parameters for estimation of time since death was performed: supravital reactions (electrical excitability of muscles, chemical excitability of muscles) and early signs of death (cooling of the body, post mortem lividity and rigor mortis) at 120 cases with known time of death. Obtained results have been used for preparation of a special table #x2013; algorithm, which contains the limit minimum and maximum values of the post mortem period for each tested parameter. The algorithm makes the work easier for the person doing the autopsy, enabling easy and fast estimation of the probable post mortem period.
Keywords: time of death; electric and chemical excitability; cooling of the body; postmortem lividity; rigor mortis